Penguatan Peran Suami Melalui Sikap dan Niat Dalam Upaya Meningkatkan Kesediaan Suami Sebagai Akseptor KB Vasektomi - Rahmawati, Dechoni; Novitasari, Rahma Kurnia; Kurniawati, Wahyu; Riyadi, Sujono (Yayasan Daarul Huda Kruengmane, 2025)
Sanden subdistrict is one of the subdistricts in Bantul Regency. Based on the preliminary study that has been conducted, the participation coverage of husbands as MOP contraceptive accepters in the District is low. Family Planning (FPA) is one of the important programs in efforts to control population growth as well as improve the well-being of families and communities. Among available contraceptive methods, MOP has been a popular choice for men who have decided to terminate their reproductive ability. MOP is a minor surgical procedure that stops the flow of sperm from the testicles to the male reproductive tract. Although this procedure is considered an effective method of birth control, there are still many factors influencing the acceptance rate and use of MOP in various communities. This dedication to the community aims to to apply Health promotion its links in an attempt to increase husbands’ participation as MOP accepters through social support factors, attitudes, and husbands’ intentions that influence a husband’s decision to accept MOP as a contraceptive method. The implementation of this activity was carried out in three stages namely preparation, implementation, and evaluation. The external result of this devotion is in the form of publication articles resulting from devotion to the public. This activity was followed by 15 participants. Based on the results of the pretest it was obtained that the average pretest score of the participants was 68 whereas after conducting the material administration and baby massage demonstration, the posttest score on the participants increased to 82.